Pemanfaatan Lemna sp. dalam Pakan Buatan untuk Meningkatkan Pertumbuhan dan Efisiensi Pemanfaatan Pakan Benih Ikan Gurami (Osphronemus gouramy) - Arofah, Nur; Herawati, Vivi Endar Herawati Endar Herawati; Sudaryono, Agung (Jurnal Masyarakat Akuakultur Indonesia, 2017)
Lemna sp. is a potential aquatic plant as alternative feed for fish, especially herbivore fish such us gourami (Osphronemus gouramy) and are plenty found in fresh water rich in nutrients. This study aimed to examine the effects of dietary different Lemna sp. meal inclusion levels on daily growth, feed efficiency and survival rate of gourami fingerlings. The study was carried out in March-June 2017 at Hatchery Fish Center, Siwarak, Ungaran. The fish used in this study was gourami fingerlings with the initial average body weight of 1.24 Â± 0.20 g/fish. The test diets used were dietary different Lemna sp. meal inclusion levels (0, 5, 10 and 15%). The experimental design used was a completely randomized design (CRD) with 4 treatments and 3 replicates. The study was carried out for 56 days, the data obtained were weight gain, total feed consumption (TFC), feed efficiency utilization (FEU), daily growth rate (DGR), protein efficiency ratio (PER), and survival rate (SR). The different inclusion levels of Lemna sp. in diets had significantly affected (P<0,05) on total feed consumption (TFC), feed efficiency utilization (FEU), daily growth rate (DGR), protein efficiency ratio (PER), and survival rate (SR) of gourami fingerlings. In conclusion, gourami fingerlings showed best performance in TFC (73.92 g), FEU (82.85%), DGR (1.09 g/day), PER (2.12%), and SR (91.11%) when the fish were feed with the diets containing 10% Lemna sp. meal.